2020
DOI: 10.21100/compass.v13i1.1022
|View full text |Cite
|
Sign up to set email alerts
|

A Socio-Cultural approach on learning in the virtual classrooms- key implications for practice

Abstract: As online classrooms have recently become integral to the teaching of Business Education in the United Kingdom (UK) and as a key challenge here is to use available resources effectively, all business teachers must be proficient in deploying virtual learning. Most international students entering Business Education do not know how to use a virtual learning environment (VLE); many are grappling with the transition to adult life, living alone and away from families. All business teachers are therefore responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Based on the findings of this study, it was determined that male and female visually impaired students have different socio-cultural perspectives. From a sociocultural point of view, students should be seen as active learners who create new social identities by taking part in communities of learning (Bhandari, 2020). It proven students with visual impairments who are male believe that sociocultural online learning has a tremendously positive effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the findings of this study, it was determined that male and female visually impaired students have different socio-cultural perspectives. From a sociocultural point of view, students should be seen as active learners who create new social identities by taking part in communities of learning (Bhandari, 2020). It proven students with visual impairments who are male believe that sociocultural online learning has a tremendously positive effect.…”
Section: Discussionmentioning
confidence: 99%
“…According to this perspective, the learning process and outcome cannot be separated from students' interactions with peers, teachers, learning resources, and relevant communities. Bhandari (2020) revealed that socio-cultural perspective maintains that students should be perceived as active learners who develop new social identities through participation in communities of learning. The sociocultural view on learning focuses on the interplay between the sociocultural environment and learning and, more specifically, on how participation in sociocultural activities influences learning (Wenger, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation